Well-being in high-rise construction sites : Key factors - Fatin Amira Sofiyya, Abd Halim; Afiqah, Radzi; Ahmad Rizal, Alias; Abdul Rahimi, Abdul Rahman (Institution of Engineering and Technology, 2022)
The working conditions in the high-rise construction industry are frequently used in the current debate due to its lack of conceptual and operational precision as the workers' well-being being unconsidered becomes work pressure. To improve this situation, understanding the key factors for workplace well-being will help create a safe and comfortable working environment for those involved in the high-rise construction industry. However, few studies have been conducted on the topic. This study aims to determine the key factors affecting construction workers' well-being in high-rise projects. To achieve those objectives, interviews and surveys with high-rise construction project employees will be conducted and analyzed. The study's findings can provide insights for developing an assessment tool for evaluating workplace well-being in high-rise construction projects. Also, the findings can be utilized as a guideline for the public and commercial sectors to guarantee that well-being practices are maintained at high-rise construction sites.